Analisis kadar fetuin-A pada pasien dengan sirosis hati di RSUP Haji Adam Malik, Medan, Indonesia - Yuni Aflah Lubis; Zulfikar Lubis; Ilhamd Ilhamd (DiscoverSys Inc., 2019)
Background: Serum Fetuin-A is produced by hepatocytes in adults and its concentration decreases during acute phase reactions in patients with liver disease. Due to it is synthesized in the liver, in some chronic liver diseases the Fetuin A levels decrease as in hepatic cirrhosis. This study aims to determine the difference between Fetuin-A levels in each severity degree in liver cirrhosis patients (Child-Pugh Score).Methods: The study was conducted in the FK USU Clinical Pathology Department / RSUP H. Adam Malik Medan in collaboration with the Gastro Entero Hepatology Division of the Internal Medicine Department FK-USU / RSUP. H. Adam Malik, Medan for the period January to April 2018. An cross-sectional observational analytic method was conducted. There were 33 people with liver cirrhosis and based on Child pugh criteria consisted of 11 cirrhosis patients with liver cirrhosis, 11 class B people, 11 class C people fulfilling the criteria inclusion. The study sample was examined by Fetuin-A and analyzed using SPSS version 17.Results: There were significant differences in fetuin A levels between groups, namely in class A liver cirrhosis of 273.87 ± 15.77 pg / ml, class B 247.43 ± 4.69 and in class C 191 ± 10.99 with a p-value was <0.000. In addition, there was a significant difference between the gender with the degree of liver cirrhosis (P <0.05) but not significantly different from the mean age and degrees of liver cirrhosis (P> 0.05)Conclusion: There were significant differences in Fetuin-A levels between patients in liver cirrhosis in all three groups based on Child-Pugh criteria. However, there was no significant difference in age between the three groups based on Child-Pugh criteria.